The Investigation of the Phenomenological YIG Phase Formation Within 1000°C to 1250°C: A Kinetic Approach. Issue 1 (24th September 2015) - Wan Ali, Wan Fahmin Faiz; Othman, Mohamadariff; Ain, Mohd Fadzil; Abdullah, Norazharuddin Shah; Ahmad, Zainal Arifin
Abstract : Presence of unwanted phase(s) such as yttrium iron perovskite (YIP) in yttrium iron garnet (YIG) ceramics has limited the utilization of YIG in the wireless communication domain. These unwanted phase(s) have been deemed responsible for the high dielectric losses, thus contributing to poor performance. This paper focuses on understanding the phenomenological phase transformation during the conventional solid state synthesis of YIG. This is done in order to monitor conditions which favor formation of unwanted phase(s), which shall later be reduced. The phase changes during YIG formation as a function of reaction times and temperatures were determined through XRD analysis. The amounts of YIG formed at various reaction times were fitted into various kinetic models in order to mathematically link what occurs experimentally to the available theoretical descriptions of reactions. It is found that the Ginstling‐Brounstein‐Habert (GBH) model exhibited good mathematical correlation to the formation of YIG. Meanwhile the activation energy ( E a ) indicated 490 kJ/mol is required for the formation of YIG. At the end, a reaction model and mechanism between Fe2 O3 and Y2 O3 were established and illustrated to underline the effect of diffusion controlled environment on the formation of phases in YIG ceramics.